Pembelajaran Desain Grafis Percetakan SMK Bina Am Ma’mur Melalui Video Blended Learning - Lusyani Sunarya; Muhammad Zaenudin; Rizza Pratama Akhpa (UNIVERSITAS RAHARJA, 2022)
Learning is an activity designed to acquire knowledge and acquire certain abilities. The success of a learning process can be seen from the existence of interesting learning methods and make students more active in learning. The previous teaching system at Bina Am Ma`Mur Vocational School was by providing material via whatsapp groups, powerpoint slides, zoom meetings and the school's website, namely bimaschool.id. This method has not been updated and does not motivate students to learn. The purpose of the observations made is to provide solutions, especially teachers in an effort to increase student motivation in the Multimedia Study Program by applying new learning methods through blended learning video media in printing graphic design subjects. This video media is considered more interesting because there are animations as well as audio and visuals that are supported by updated and complete information that supports Printing Graphic Design subjects. Research methods: Data Collection, Media Design with the Adobe After Effect Pro CC 2020 application, Clip Studio Paint EX 1.8.8 and Adobe Premiere Pro CC 2020. That way students will be more interested and the learning process can be more fun during the COVID-19 pandemic. 19, then the learning motivation of the students can increase and better understand the subjects of Printing Graphic Design. Keywords—Blended Learning; Information; Schools Belajar adalah kegiatan yang dirancang untuk memperoleh pengetahuan dan memperoleh kemampuan tertentu. Keberhasilan suatu proses pembelajaran dapat dilihat dari adanya metode pembelajaran yang menarik dan menjadikan siswa lebih aktif dalam belajar. Sistem pengajaran sebelumnya pada SMK Bina Am Ma`Mur dengan memberikan materi melalui whatsapp group, slide powerpoint, zoom meeting dan website Sekolah yaitu bimaschool.id. Metode ini belum update dan kurang memotivasi belajar siswa/i. Tujuan observasi yang dilakukan adalah untuk memberikan solusi khususnya Guru dalam upaya meningkatkan motivasi belajar siswa/i Program Studi Multimedia dengan menerapkan metode pembelajaran baru melalui media video blended learning pada mata pelajaran desain grafis percetakan. Media video ini dinilai lebih menarik karena terdapat animasi serta audio dan visual yang didukung dengan informasi update dan lengkap yang mendukung mata pelajaran Desain Grafis Percetakan. Metode penelitian: Pengumpulan Data, Perancangan Media dengan aplikasi Adobe After Effect Pro CC 2020, Clip Studio Paint EX 1.8.8 dan Adobe Premiere Pro CC 2020. Dengan begitu siswa/siswi akan lebih tertarik dan proses belajar bisa lebih menyenangkan di masa pademi covid-19 ini, kemudian motivasi belajar para siswa/siswi dapat meningkat dan lebih memahami mata pelajaran Desain Grafis Percetakan. Kata Kunci—Blended Learning; Informasi; Sekolah